2014
DOI: 10.1371/journal.pone.0102704
|View full text |Cite
|
Sign up to set email alerts
|

BNP but Not s-cTnln Is Associated with Cardioembolic Aetiology and Predicts Short and Long Term Prognosis after Cerebrovascular Events

Abstract: BackgroundWe analyzed the prognostic value of b-type natriuretic peptide (BNP) and sensitive cardiac Troponin (s-cTnI) in patients with ischemic stroke or transient ischemic attack (TIA) and their significance in predicting stroke aetiology.MethodsIn a prospectively enrolled cohort we measured BNP and s-cTnI levels upon admission. Primary endpoints were mortality, unfavorable functional outcome and stroke recurrence after 90 days and after 12 months. Secondary endpoint was cardioembolic aetiology.ResultsIn 441… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
3
26
0
2
Order By: Relevance
“…23 Recently, BNP and NT-pro-BNP were both found to be associated with incident stroke in a community-based sample free of stroke at baseline. 16 In this study, NT-pro-BNP was the protein on the chip by far being most closely related to stroke risk, despite adjustment for atrial fibrillation at baseline.…”
mentioning
confidence: 99%
“…23 Recently, BNP and NT-pro-BNP were both found to be associated with incident stroke in a community-based sample free of stroke at baseline. 16 In this study, NT-pro-BNP was the protein on the chip by far being most closely related to stroke risk, despite adjustment for atrial fibrillation at baseline.…”
mentioning
confidence: 99%
“…Cardioembolic strokes are more severe and have worse outcome than noncardioembolic strokes27, 28; therefore, it is tentatively postulated that the beneficial effect of BNP could be masked in these subtypes of strokes.…”
Section: Discussionmentioning
confidence: 99%
“…BNP receptors are widely expressed in the brain, and BNP has been found in different cerebral regions such as hypothalamus or cerebral cortex,1, 15, 17, 28 for instance. However, BNP‐mRNA has not been detected in cerebral tissue, suggesting a peripheral origin of this peptide 1, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of this observation remains to be explored in further studies. A recent study in 447 patients with ischemic stroke and transient ischemic attack demonstrated that BNP improved the diagnostic accuracy for identifying the cardio-embolic etiology of the stroke [28], suggesting that BNP can be valuable tool in the stroke setting for the identification of patients who could potentially benefit from interventions aimed at preventing repeated embolization events. Emboli originating from heart atria can cause occlusion of major cerebral arteries, resulting in extensive cerebral infarction that is accompanied by severe neurological impairment.…”
Section: Discussionmentioning
confidence: 99%